SISTEM PAKAR UNTUK MENDETEKSI PENYAKIT JANTUNG KORONER MENGGUNAKAN FUZZY-MAMDANI - Moch. Bayu Noviantoro; Priyo Sidik Sasongko (Jurnal Matematika, 2013)
Expert system is a system basic computerize which use knowledge, fact, and intellectual activity to solve problem as usually can be solve by an expert on that field. Application of fuzzy – Mamdani method on expert system purpose to explain expert knowledge on not absolute, not complete and so complicated field. One of expert system application is to detect heart coronary disease. Heart coronary disease is the first killer in Indonesia. The number of  patients is so many maked the role of medical personnel often have limitation in detecting heart coronary disease. In this final paper has been made expert system application program in detecting heart coronary disease by fuzzy – Mamdani. Risk factors that influence heart coronary disease are age, LDL, total cholesterol, HDL, triglycerides, sistolik blood pressure, and diastolik blood pressure. Based on that risk factors will be obtained output which is risk percentage a person who is infected heart coronary disease. Keywords : Expert system, fuzzy – Mamdany, heart coronary disease